PUBLIC SERVICE MALLS AS A SOLUTIION IN IMPROVING THE QUALITY OF PUBLIC SERVICES IN INDONESIA - Putri Wulandari Atur Rejeki (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2022)
One of public service transformation carried out by the government is by building Public Service Malls (PSM). To date, more than 30 regencies/cities have had PSM. This study aims to analyze the extent to which the PSM built by the regencies/city government is significantly able to improve public services in the region. The study uses a quantitative method by comparing the quality of public services as measured by the value of the Public Service Index (PSI) in 2020 for groups of regencies/cities that already have PSM (30 regions) with groups that do not yet have PSM (191 regions). The normality test for the group of regencies/cities that do not yet have PSM shows the p-value of the Kolmogorov-Smirnov of 0.001. This means that the regional group is not from a normal population. The Mann-Whitney test was used to continue data analysis. The results of the Mann-Whitney Test were 2145,500 with a p-value of 0.027 (2-tailed, =0.05). The study found that the quality of public services provided by government regencies/cities that have a PSM is significantly better than those without a PSM. The most important factor in improving the quality of regencies/city government public services in Indonesia is the service policy.